Perancangan Sistem Informasi Manajemen pada Klinik Skala Kecil (Studi Kasus: Klinik Dr. Jonni) - Ayuliana, Ayuliana; Wijaya, Stanislaus Steven; Lawunugraha, Lawrentius Siangjaya; Iswanto, Irene Anindaputri (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The purpose of this research was to develop a database application at dr. Jonni clinic which can be used for processing and recording of operational data with an attractive user interface. Through the integrated database application, data on dr. Jonni clinic would be more structured, therefore data retrieval will go faster and more accurate, data security administration will be increased, data redundancy will be eliminated and service performance clinic dr. Jonni will also be increased. The method of analysis includes the study of literature, examination of documentation, observation, and interviews. While in the design, the method includes application design using the waterfall method models, database design and data modeling application screens using State Transition Diagrams. The results achieved from this research is an application of data base management hospital. With database applications, all data and information can be integrated well, so that it would improve the quality of  services as well as facilitate storing and accessing data. The conclusions obtained from this research is the application of data base management hospital helps in generating quick and accurate information that is used to support operations and decision-making in the clinic dr. Jonni.